Design and Implementation of Server Room Controlling using the Fuzzy Sugeno Method - Dewi Anjani; Tegar Palyus Fiqar; Riska Kurniyanto Abdullah (Jurnal Teknologi dan Manajemen, 2024)
The standard security for a good server room in an institution includes the monitoring processes of humidity, temperature, and smoke levels in the server room. Based on this issue, a device is needed to perform real-time monitoring of the server room and can be accessed online using Internet of Things (IoT) technology based on Wemos D1 R2, DHT22 sensor, MQ2 sensor, and infrared sensor. This system has a level of uncertainty for each DHT22 sensor in measuring temperature. For DHT22 sensor (∑), it obtains a measurement uncertainty value of 0.22%. DHT22 sensor (Δ) has an uncertainty of 0.22%, and DHT22 sensor (α) has an uncertainty of 0.50%. Then, for the level of uncertainty for each DHT22 sensor in measuring humidity, DHT22 sensor (∑) has a measurement uncertainty of 1.85%. DHT22 sensor (∆) has an uncertainty of 2.22%, and DHT22 sensor (α) has an uncertainty of 4.80%. The method used is fuzzy logic Sugeno to provide output for the AC on and off states. Furthermore, an analysis and implementation of the ISO:27001 security standard are conducted in the server room of Institut Teknologi Kalimantan by maintaining the room temperature between 20-25°C and humidity between 40-55%. However, there are differences in temperature and humidity readings between the device and the thermometer used to measure the room conditions. Therefore, it is necessary to adjust the temperature membership range to 18-27°C and the humidity membership range to 40-80%. Then, a threshold of 2196.8383 ppm is set for the MQ2 sensor to detect small-scale smoke.